2023
DOI: 10.1371/journal.pgph.0001789
|View full text |Cite
|
Sign up to set email alerts
|

Facility-based care for moderately low birthweight infants in India, Malawi, and Tanzania

Abstract: Globally, increasing rates of facility-based childbirth enable early intervention for small vulnerable newborns. We describe health system-level inputs, current feeding, and discharge practices for moderately low birthweight (MLBW) infants (1500-<2500g) in resource-constrained settings. The Low Birthweight Infant Feeding Exploration study is a mixed methods observational study in 12 secondary- and tertiary-level facilities in India, Malawi, and Tanzania. We analyzed data from baseline facility assessments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 14 Key study results related to in-facility feeding practices and 6-month prospective cohort outcomes have been published elsewhere. 15 …”
Section: Methodsmentioning
confidence: 99%
“… 14 Key study results related to in-facility feeding practices and 6-month prospective cohort outcomes have been published elsewhere. 15 …”
Section: Methodsmentioning
confidence: 99%
“…This study was a component of the Low Birthweight Infant Feeding Exploration (LIFE) study, an observational cohort study that aimed to document the current feeding practices and growth patterns among LBW infants in LMICs in order to inform feeding interventions. Additional information about the cohort study methods can be found in the protocol [ 34 ], in the paper documenting infants’ feeding practices, growth patterns, and risk factors for growth outcomes at six months [ 35 ], and in a paper describing facility-based care for moderately low birthweight infants in these settings [ 36 ]. This paper reports findings related to WASH and IPC from two data streams: the facility needs assessment and the feeding preparation observation data as part of the in-facility observational cohort.…”
Section: Methodsmentioning
confidence: 99%